Circularly Polarized Proximity-Fed Microstrip Array Antenna for Micro Satellite - Muhammad Darsono; Endra Wijaya (Universitas Ahmad Dahlan, 2013)
Design of circular polarization microstrip antenna array was developed to support micro-satellite technology. Circular polarization antenna array used for data transmission applications operating in the S band frequencies from the satellite to the ground station. In this study of the patch array using proximity coupling techniques in this study to obtain high gain and wide of bandwidth. The structure of the antenna array design consists of four identical square patch elements and to use the concept of corporate transmission line fed power divider network uses three transformers quarter-lambda T-junction. Bandwidth impedance matching for resonance between two patches is ¾ l antenna system for center frequency of 2.25 GHz. The antenna is designed using the method of moments through simulation with microwave office software applications. The results of simulations and measurements obtained antenna parameters, such as: bandwidth of return loss <-10 dB above 100 MHz resonant frequency shifted to 1.75%, VSWR (1 to 2), the bandwidth of axial ratio <3 dB is 1.6% (narrowband) and the maximum directivity (gain) is 9.128 dB. Overall study results showed good performance antenna array with circular polarization properties, high gain and operates in the S band frequency micro satellite system.